Geochemical Assessment of some water Resources in Obio Akpor and Port Harcourt, Niger Delta Basin, Nigeria - Onwualu-John, J. N.; Offodile, O. P. (European Journal of Applied Sciences, 2022)
Assessment of heavy metal concentrations in water resources within Obio-Akpor and Port Harcourt local government area of Rivers State in Niger Delta, Nigeria was carried out. Five water samples were obtained from Station 1 surface water, four water samples were acquired from Station 2 surface water and three groundwater samples were obtained from Station 3. The physiochemical parameters analyzed were pH, Temperature, Electrical conductivity, Total dissolved solids and Turbidity while the heavy metals analyzed were Total Iron, Lead, Copper, Nickel, Manganese, Zinc, Chromium, Cadmium and Cobalt. The analysis shows that the pH value for Station 1 ranges from 4.73 - 6.25, Station 2 pH value ranges from 5.72- 6.27 and Station 3 pH value ranges from 4.55 - 5.55. The mean concentration of heavy metals in Station 1 shows an increasing order of Cd>Cr>Co>Cu>Fe>Pb>Mn>Zn>Ni. The mean concentration of heavy metals for Station 1 shows that Lead (0.771mg/l) and Nickel (0.2522mg/l) are above the WHO and SON standards. The mean concentration of heavy metals in Station 2 shows an increasing order of Cd>Cr>Pb>Cu>Ni≥Co>Fe>Zn>Mn. The mean concentration of heavy metals for Station 2 shows that Lead (0.02325mg/l) and Nickel (0.035mg/l) are above the WHO and SON standard. The mean concentration of heavy metals obtained in the Station 3 shows an increasing order of Cd≥Cr>Ni≥Co>Fe>Mn>Zn>Pb>Cu. The mean concentration of heavy metals for Station 3 shows that Lead (0.044333mg/l) is above the WHO and SON standard. Water quality and pollution index shows that the water quality in all the Station is not suitable for consumption. Pollution index indicates that in station 1 and 2, Nickel and lead are the major pollutants in the water while in station 3, lead is the only major pollutant in the water. In as much as these heavy metals are accumulating, over time they become highly toxic to health.